Association between human papilloma virus/Epstein–Barr virus coinfection and oral carcinogenesis. (18th July 2014) - Jiang, Ru; Ekshyyan, Oleksandr; Moore‐Medlin, Tara; Rong, Xiaohua; Nathan, Sean; Gu, Xin; Abreo, Fleurette; Rosenthal, Eben L.; Shi, Mingxia; Guidry, Joseph T.; Scott, Rona S.; Hutt‐Fletcher, Lindsey M.; et al.
<x xml:space="preserve">Abstract</x> Background The recent epidemic of head and neck squamous cell carcinomas associated with human papilloma virus (HPV) has not addressed its association with lymphoid tissue in the oropharynx or the potential role of Epstein–Barr virus (EBV)/HPV coinfection. Methods The prevalence of HPV and EBV infection/coinfection and CD21 mRNA expression were determined in normal and cancerous tissues from the oropharynx using in situ hybridization (ISH), p16, and quantitative reverse transcriptase PCR (qRT‐PCR). The effects of coinfection on tumorigenicity were evaluated using proliferation and invasion assays. Results Normal oropharynx, tonsil, non‐cancer base of tongue (BOT), and BOT from sleep apnea patients demonstrated EBV positivity ranging from 7% to 36% depending on the site and methods of detection used (qRT‐PCR or ISH). Among non‐malignant BOT samples, HPV positivity was noted only in 20%. The percent of tonsil and BOT cancers positive for HPV (up to 63% and 80%, respectively) or coinfected with HPV/EBV (up to 25% and 70%, respectively) were both significantly associated with cancer status. Notably, HPV/EBV coinfection was observed only in malignant tissue originating in lymphoid‐rich oropharynx sites (tonsil, BOT). CD21 mRNA (the major EBV attachment receptor) was detected in tonsil and BOT epithelium, but not in soft‐palate epithelium. Coinfected cell lines showed a significant increase in invasiveness (P < 0.01). Conclusions There is a high prevalence of HPV/EBV infection and coinfection in BOT and tonsil cancers, possibly reflecting their origins in lymphoid‐rich tissue. In vitro, cells modeling coinfection have an increased invasive potential.